Evaluation of desalination costs with DEEP. (4th October 2004) - Nisan, S.; Volpi, Linda
Detailed analysis has shown several discrepancies and pitfalls of coupling an economic evaluation code, such as SEMER to the desalination cost evaluation code DEEP. This paper resumes our findings, which may be of interest to other DEEP users. The paper in particular deals with the following issues: why is it that power costs from nuclear systems are systematically higher in DEEP than those given by the economic evaluations made by individual organisations, (in our case, the SEMER code for example), even when the calculated construction costs are input into DEEP? Why corresponding power costs for fossil energy systems are lower? Why in particular desalination costs from Gas-Turbine Combined Cycle power system, which is now considered to be the cheapest fossil fuel option, are higher than desalination costs by Pulverised Coal system? Why DEEP calculation results with the backup heat source are 40% higher than those without the backup heat source?